Politik Mahar Di Indonesia: Antara Ada dan Tiada - Anak Agung Ngurah Agung Wira Bima Wikrama (Jurnal Ilmiah Cakrawarti, 2018)
Political parties are the only institution that has the right to propose candi- dates for president and vice president as stipulated in Article 6A paragraph 2 of the 1945 Constitution so that they will have power and legitimacy as heads of state and heads of government. These constitutional rights are not owned by any democratic institution other than political parties. However, in the process of holding the general election, it does not always go as expected, as stated in the KPU’s laws and regulations. There were irregulari- ties committed by candidates and by political parties in the form of Money Politics.According to the political dowry event is in the general election area based on the legal principle of Lex specialis derogat legimitation generaly which states that the law is specific (lex specialis) overrides the general law (lex generalis) the Money Politic event is resolved by an institution, namely Bawaslu (General Election Supervisory Board).Besides the Article 6A paragraph 2 of the 1945, there is also Law Number 10 of 2016 concerning the Second Amendment of Law No. 1 in 2015 concerning the stipulation of Perppu (the governmental regulation of low amandement) Number 1 in 2014 according to the governor’s election, regents and mayors, especially in Article 47, Article 187A,Article 187B, Article 187C and Article 187D which regulates general elections. But in reality there are many irregularities in the implementation of the Constitution and etc.Events in the form of political dowry still occured which is evidenced by the infor- mation given by several witnesses and as the victim and perpetrator of the political dowry. Surprisingly, the General Election Supervisory Board (Bawaslu) as an election watchdog institution mandated by the Act to enforce the prevailing regulations is very difficult to carry out its duties, reminding that Bawaslu has weaknesses in handling the alleged polit- ical dowry. The weakness of Bawaslu is that they do not have the power to take witnesses or people who will be questioned.The author argues that there is a need for a legal protection in the form of a law that provides better opportunities to Bawaslu so that the position of Bawaslu as an election supervisory bord can be much stronger.